2010
DOI: 10.1165/rcmb.2009-0068oc
|View full text |Cite
|
Sign up to set email alerts
|

Conditional Overexpression of Connective Tissue Growth Factor Disrupts Postnatal Lung Development

Abstract: Connective tissue growth factor (CTGF) is a member of an emerging family of immediate-early gene products that coordinates complex biological processes during development, differentiation, and tissue repair. Overexpression of CTGF is associated with mechanical ventilation with high tidal volume and oxygen exposure in newborn lungs. However, the role of CTGF in postnatal lung development and remodeling is not well understood. In the present study, a doubletransgenic mouse model was generated with doxycycline-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 55 publications
2
42
0
1
Order By: Relevance
“…CTGF has recently been shown to be sufficient (30) and required for murine hyperoxia-induced neonatal lung injury (2). We tested whether CTGF could be responsible for GSK-3␤/␤-catenin-mediated myofibroblastic differentiation in our model, as well in infants with BPD.…”
Section: Transduction Of Mscs With Gsk-3␤ S9a a Nonphosphorylatable mentioning
confidence: 99%
“…CTGF has recently been shown to be sufficient (30) and required for murine hyperoxia-induced neonatal lung injury (2). We tested whether CTGF could be responsible for GSK-3␤/␤-catenin-mediated myofibroblastic differentiation in our model, as well in infants with BPD.…”
Section: Transduction Of Mscs With Gsk-3␤ S9a a Nonphosphorylatable mentioning
confidence: 99%
“…Multiple studies have examined the potential role of CTGF in experimental BPD and demonstrated that increased CTGF expression is associated with chronic hyperoxia as well as mechanical ventilationinduced lung injury in neonatal rodents (6-10). Recent studies from our laboratory utilizing genetic gain-of-function and biological loss-of-function approaches have provided compelling evidence that a novel signaling network orchestrated by CTGF plays an important role in BPD pathogenesis (6,11,12). In our novel transgenic mouse model, targeted overexpression of CTGF in alveolar type II epithelial (AT II) cells induces the pathological hallmarks of severe BPD, including decreased alveolar and vascular development and increased vascular remodeling and PH (12).…”
mentioning
confidence: 99%
“…Septal thinning is accompanied by remodeling of the capillary network with a reduction in septal interstitial extracellular matrix proteins and closer apposition between capillaries and the type-1 epithelium (9). Septal thickening that accompanied overexpression of connective tissue growth factor during P1-P14 seemed to inhibit alveolar capillary formation (10). Understanding the thinning process is important because thickened walls are observed in mechanically ventilated lungs of children (11) and baboons (12) with bronchopulmonary dysplasia (BPD).…”
mentioning
confidence: 99%